Práticas de cuidado em uma unidade de saúde da família: contribuições para a formação de enfermeiros - Alberti, Gabriela Fávero (2014)
This work aims to inform about nursing care practices in a Family Health Center and its contribution to the reflection on academic nursing education. The method of this research was done through a qualitative case study approach. Part of the information was collected from a database from February to July 2012. The research was conducted at a Family Health Center in the City of Santa Maria/RS with two multidisciplinary teams and a dental health team. The data collected was composed of semi-structured interviews with nurses, participant observation with diary records of the care practices performed and documenting researches such as minutes from team meetings and records from information storage system. The analysis and interpretation of data were guided by the Operational Proposal with two operational moments, exploratory and interpretative. In relation to the second moment, three steps were performed: the Data Organization, all the material was organized in a specific order and performed according to database construction; the Data Classification, from dense and exhaustive readings and using the attributes of Primary Care as background, it was possible to construct the analytical categories; and the Final Analysis, considering a dialectical movement between the empirical and theoretical material, or vice versa. This study was approved by the Ethics Committee, Protocol 1939/11, in which the principal researcher consented to the use of data by signing the Authorization Term for Database Using. The results were presented in two articles. First, the analysis of care practices regarding the first contact attribute. It helped to alert to the academic education the necessity of interaction between nurses and other professionals, favoring an academic student to acquire more skills for the interdisciplinary team work. In addition, it stimulates on a student an opening for new sensibilities with a view on the development of abilities that can be translated in comprehension attitudes of others and investigate the pro-active behavior in a way that the student assumes their authentic participation in the act of meeting and reflecting about what is being naturalized, building their formative way. Second, the focus was on the longitudinality attribute. Guided to the care practices for specific situations of certain users at different times of data collection. In this sense, the academic education should provide a variety of scenarios for a student to meet other contexts and the relationships between people and their surroundings; It should also encourage the development of information skills in values such as solidarity, accountability and inter-subjective understanding of people in which care is addressed; and, finally, encourage a student to understand the dialectical relationship between "managing" and "care" and the straight relation with the quality of care. As effects of this new bias in education, we have the transformation of care practices and also the formation of new professionals with collective consciousness, able to face the complexity, daring to invent new practices and ethical-political-sensitive whose health care model to achieve is care. It indicates that by knowing the practice of nurses, it was possible to think some ways whose academic education does not lose focus on the centrality of the student in order to make them protagonist and challenge them to be proactive in building the professional and be hence the construction of an identity with "being a nurse", emphasizing that more studies with this subject should be performed.